Решите уравнение используя метод замены переменной.


Решите уравнение используя метод замены переменной.

alidagalamova2003 alidagalamova2003    2   20.01.2021 15:06    3

Ответы
пандочка94 пандочка94  19.02.2021 15:07

x(x+1)(x+3)(x+4) = 40

x(x+4)\cdot (x+1)(x+3) = 40

(x^2 + 4x)\cdot (x^2 + 3x + x + 3) = 40

(x^2 + 4x)\cdot (x^2 + 4x + 3) = 40

t = x^2 + 4x

t\cdot (t+3) = 40

t^2 + 3t = 40

t^2 + 3t - 40 = 0

D = 3^2 - 4\cdot 1\cdot(-40) = 9 + 160 = 169 = 13^2

t = \frac{-3\pm 13}{2}

t_1 = \frac{-3-13}{2} = \frac{-16}{2} = -8

t_2 = \frac{-3+13}{2} = \frac{10}{2} = 5

1)

x^2 + 4x = -8

x^2 + 4x + 8 = 0

D = 4^2 - 4\cdot 8 = 16 - 32 = -16 < 0

в 1) решений нет.

2) x^2 + 4x = 5

x^2 + 4x - 5 = 0

D = 4^2 - 4\cdot (-5) = 16 + 20 = 36 = 6^2

x = \frac{-4\pm 6}{2} = -2\pm 3

x_1 = -2-3 = -5

x_2 = -2+3 = 1

ответ. {-5; 1}.

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика